Analisis Ketepatan Triage Pada Pasien di Instalasi Gawat Darurat - Sholehah, Baitus; Laili, Anisa Nur; Azizah, Arika (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Triage nurses have an important role to save patients, patients who come to the emergency department are stabilized and categorized based on severity. The accuracy of triage is a guarantee of patient safety. The purpose of this study was to analyze the relationship between the level of nurse knowledge and the accuracy of triage in patients in the emergency department. The research design in this study used a quantitative research design with a cross sectional approach. Research data were collected using a research instrument with a questionnaire of nurse knowledge and Standard Operational Procedure (SOP) triage accuracy. Data were analyzed with the SPSS program presented in the form of frequency tables and cross tables to analyze the relationship between the level of knowledge and accuracy of triage. Data analysis using Kendall's test. The results of the study obtained a Sig. (2-tailed) of 0.000 (<0.005), it can be concluded that there is a relationship between the level of nurse knowledge and the accuracy of triage in patients. The Correlation Coefficient value is positive at 0.648, it can be concluded that the direction of the relationship between the two variables is unidirectional and has a strong relationship, this shows that a good level of nurse knowledge will affect the accuracy of appropriate triage, in this case the nurse's knowledge about triage is very important and needs to be improved so that the accuracy of triage is in accordance with the patient's condition.